Soil biological health and yield outcomes from integrating conservation agricultural practices in a corn–soybean system are dependent on environment - Benjamin K. Agyei; Laura E. Lindsey; Maninder P. Singh (Agrosystems, Geosciences & Environment, 2026)
Abstract Research examining the integration of conservation agricultural practices and their medium‐term effects on crop productivity and soil health remain limited within the corn ( Zea mays L.)—soybean [ Glycine max (L.) Merr.] system of northern US. We evaluated the impact of integrating no‐till (NT), biochar (BC), cover crops (CCs), and nitrogen management (NM) on corn yield and soil microbial abundance at one site in Michigan (MI) and two in Ohio (OH) after 4 years. BC was applied at 10 Mg ha −1 in fall 2020. The CC treatment included cereal rye (Secale cereale L.) in 2021 and 2023, and winter wheat (Triticum aestivum L.) in 2022. NM involved single or split applications of 146–212 kg N ha −1 during the corn phase and a uniform 132 kg N ha −1 during the wheat phase. A conservation practice index was estimated to represent the level of integration of the four practices, resulting in five levels (0–4) at MI and four levels (1–4) at OH. Corn yield did not improve significantly with increasing index across locations. However, specific combinations provided site‐dependent benefits. The addition of CC to NT improved yield by 10% compared to adding NM to NT at the MI location. At one OH location, NT + BC yielded 25% more than NT + CC. Fungi and arbuscular mycorrhizal (AM) fungi populations increased with increasing conservation practice index at MI and one OH site. Overall, our study shows that adding either CC or BC to a NT system can enhance corn yield and improve soil biological health.